Antioxidants of plant origin in cosmetic products: Physicochemical properties and photoprotective potential - Martić Radava; Krajišnik Danina; Milić Jela (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
It is known that long-term exposure to ultraviolet (UV) radiation causes skin redness, solar erythema or burns, affects the structure of dermal connective tissue, increases the production of free radicals and the expression of matrix metalloproteinases, and can lead to the development of skin cancer. The World Health Organization recommends protective measures from the adverse effects of UV radiation, including the topical application of sunscreen products. One of the strategies for improving the quality and effectiveness of sunscreen products is introduction of new, more efficient and safer active molecules that absorb, reflect or disperse UV photons, as well as the introduction of substances that can prevent, neutralize or even repair damage caused by UV radiation. Significant potential for skin protection against harmful UV radiation is recognized in plant origin substances, which primarily exhibit an antioxidant effect, and additionally possess other photoprotective properties, which makes them interesting for further investigation. This paper presents an overview of the physicochemical properties of plant-based antioxidants, which are important for the formulation of the final cosmetic product and an overview of the potential effects of these substances in skin protection against UV radiation.